Frequency of Acute Hepatitis in Children with Enteric Fever of Age 1 to 10 Years Presenting to Ayub Teaching Hospital Abbottabad - Khan, Salman; Najeeb, Shahzad; Ali, Armaghan; Khalid, Maria (Indus Journal of Bioscience Research, 2025)
Background: Acute hepatitis in children with enteric fever remains a significant public health concern, with varying prevalence across different populations. The association between demographic factors and the prevalence of acute hepatitis in children with enteric fever has yet to be fully explored. Objective: To determine the frequency of acute hepatitis in children with enteric fever of age 1 to 10 years presenting to Ayub Teaching Hospital Abbottabad. Study Design: Cross-sectional observational study. Duration and Place of Study: The study was conducted from May 2024 to November 2024 at the Department of Pediatrics, Ayub Teaching Hospital, Abbottabad. Methodology: A total of 102 children aged 1–10 years, diagnosed with enteric fever (fever ≥101°F for 4 days with positive blood culture for S. Typhi), were included. Children with a history of malaria, pneumonia, liver disorders, or immunocompromised states were excluded. Blood samples were analyzed for liver enzyme levels and real-time PCR to confirm viral hepatitis (HBV, HCV, HAV, HEV). Results: The mean age of participants was 5.84 ± 2.16 years, with a mean weight of 8.27 ± 3.51 kg. Acute hepatitis was diagnosed in 16 patients (15.7%), with the types being HBV (2%), HCV (5.9%), HAV (4.9%), and HEV (2.9%). Rural residence was associated with a higher prevalence of acute hepatitis (27.5% vs. 8.1% in urban areas, p = 0.012). Conclusion: This study highlights acute hepatitis as a major health concern in children, with Hepatitis A as the leading cause. Elevated liver enzymes contribute to acute liver failure. Public health interventions, including improved sanitation and accessible care, are essential to mitigate the disease’s impact on children.